KEKUATAN HUKUM PERJANJIAN LISAN APABILA TERJADI WANPRESTASI (STUDI PUTUSAN NOMOR 1176/PDT.G/2020/PN SBY) - Kelanit, Antonia Junianti Hendrieta (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
This research focuses on the power of oral agreements in the event of default. The purpose of this study is to find out more about the legal strength of oral agreements by racing against the judge’s consideration of the act of default in the Surabaya District Court Decision Number 1176/Pdt.G/2020/PN. Sling. The agreement binds the parties therein to carry out what has been mutually agreed upon in the agreement so as to have legal consequences for the parties involved in it. In Indonesia, the legal provisions of the agreement are regulated in the Civil Code contained in Book III on Perikatan. It is not clearly determined whether the agreement should be formed in a script (written) but rather frees the party concerned to determine for himself the form of the agreement he wants as long as it does not conflict with the applicable provisions. However, of course, there are various agreements that require it to be made in written form for clearer legal certainty, especially in terms of proof in the event of a Default or Default so that the legal force is more guaranteed. Oral agreements made are actually weak if they are not supported by strong evidence such as in written agreements